Effectiveness of Further Vocational Training in Germany - Empirical Findings for Persons Receiving Means-tested Unemployment Benefits - Bernhard, Sarah [Verfasser]; Kruppe, Thomas [Verfasser] (My University, 2012)
"Further vocational training for the unemployed aims at enhancing their job prospects. This paper analyzes the effectiveness of subsidized training programs for means-tested unemployment benefit recipients in Germany. The empirical findings are based on rich administrative data from the German Federal Employment Agency using propensity score matching to construct a suitable comparison group. We consider the initiation of training in early 2005, just after the reform of the German means-tested benefit system, which aimed at activating hard-to-place job-seekers, and after the introduction of a voucher system as the sole assigning mechanism for vocational training. We estimated the effects of vocational training for several groups differentiated by age, gender, migration background, skills, program duration, length of time since last job and differences between East and West Germany. As a result, we show that vocational training has a considerable beneficial impact on participants as it raises the employment rate in the intermediate term by up to 13 percentage points, and – with a slightly lower impact – it reduces the number of unemployment benefit II recipients." (Autorenreferat, BIBB-Doku)

"Geförderte berufliche Weiterbildung soll die Beschäftigungschancen von Arbeitslosen erhöhen. Diese Studie analysiert die Effektivität geförderter beruflicher Weiterbildung für Empfänger von Arbeitslosengeld II in Deutschland. Die empirischen Ergebnisse basieren auf administrativen Daten der Bundesagentur für Arbeit. Mittels Propensity Score Matching wird eine Vergleichsgruppe für die Teilnehmer gebildet. Die Studie betrachtet Eintritte in geförderte berufliche Weiterbildung Anfang des Jahres 2005, direkt nach der Einführung des SGB II, das besonders auf die stärkere Aktivierung von Problemgruppen des Arbeitsmarktes abzielt. Zudem war zu dieser Zeit auch schon der Bildungsgutschein als einziger Zuweisungsmechanismus zu beruflicher Weiterbildung eingeführt worden. Die Studie berücksichtigt Effekte beruflicher Weiterbildung für verschiedene Gruppen differenziert nach Alter, Geschlecht, Migrationshintergrund, Qualifikation, Dauer der Weiterbildung und Dauer seit der letzten Beschäftigung sowie Unterschiede zwischen Ost- und Westdeutschland. Als Ergebnis zeigt sich, dass sich berufliche Weiterbildung für die Teilnehmer lohnt: Sie erhöht mittelfristig deren Anteil in Beschäftigung um bis zu 13 Prozentpunkte und reduziert – wenn auch in geringerem Ausmaß deren Anteile im Arbeitslosengeld-II-Bezug." (Autorenreferat, BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; S 4.3.6 Human Capital; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.2.2.4 Arbeitslosigkeit; Weiterbildungsförderung; Berufliche Weiterbildung; Arbeitsloser; Bildungsertrag; Arbeitsmarktchance; Empirische Untersuchung